MAKING SENSE OF THE WAYS WE MAKE SENSE OF THE PAST: THE PERIODO PROJECT. - RABINOWITZ, ADAM; SHAW, RYAN; BUCHANAN, SARAH; GOLDEN, PATRICK; KANSA, ERIC (Bulletin of the Institute of Classical Studies, 2016)
The PeriodO project seeks to fill a gap in the landscape of digital antiquity through the creation of a Linked Data gazetteer of period definitions that transparently record the spatial and temporal boundaries assigned to a given period by an authoritative source. Our presentation of the PeriodO gazetteer is prefaced by a history of the role of periodization in the study of the past, and an analysis of the difficulties created by the use of periods for both digital data visualization and integration. This is followed by an overview of the PeriodO data model, a description of the platform's architecture, and a discussion of the future direction of the project.